Prognostic impact of anemia in acute coronary syndrome patients. (2nd May 2022) - Carvalho, P; Monteiro, J; Carvalho, C; Bernardo, M; Fontes, P; Mateus, P; Goncalves, F; Moreira, I
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Anemia commonly accompanies acute coronary syndromes (ACS) and is associated with worst outcomes. Over the last decade several trials have investigated the prognostic impact of hemoglobin (Hb) levels in the context of acute coronary syndrome (ACS), both in the short-term, during hospitalization, and in the long-term, albeit mainly up to three months, with only a few trials assessing one-year outcomes. Methods: This was a retrospective study of ACS patients admitted to a single center between October/2011 and September/2018, in whom Hb level was evaluated on admission. Anemia was defined as defined as Hb ≤ 13g/dL for males and Hb ≤ 12g/dl for females. Baseline characteristics, management, and outcomes were compared between patients with and without anemia. The primary endpoint, MACE, was a composite of acute coronary syndrome, stroke and global death events. The secondary endpoint was cardiovascular death. Results: A total of 578 patients were selected, with a mean age of 66.7±13.1 years, 74.9% were male, 42.6% had a ST-Elevation Myocardial Infarction and 18.9% met criteria for anemia. These patients had more comorbidities: arterial hypertension (78.0% vs 60.6%; p=0.001), diabetes mellitus (25.7% vs 50.5%, p=0.001), peripheral artery disease (3.9% vs 10.1%, p=0.01) and were older (mean age 64.8±13.1 vs 72.1±11.0 years, p<0.001). The non-anemic group had a higher percentage of smokers and, during hospitalization, was more often submitted to percutaneous coronary angioplasty. Antithrombotic therapy given during hospitalization and on discharge was similar in both groups. During a median follow-up of 41 months (IQR: 20-59), 91 patients (15.7%) died and 104 (18%) had a MACE event. In a multivariate regression analysis, after adjusting for possible confounders, anemia was an independent predictor of MACE events (HR 1.64, 95% CI: 1.07-2.50) and cardiovascular death (HR 2.24, 95% CI: 1.26-3.96). Conclusion: Anemia is highly prevalent in the ACS setting and the presence of anemia was independently associated with worse outcomes, particularly mortality.